Applying the Hadith on Cleanliness in Eco-Theological Islamic Education at Community Learning Centers (PKBM): Penerapan Hadis Kebersihan dalam Pembelajaran PAI Berbasis Ekoteologi di Pusat Kegiatan Belajar Masyarakat (PKBM) - Murtadoilah, Hendi; Rusmidi, Didi (Medpro, 2025)
Islamic Religious Education (PAI) in Community Learning Centers (PKBM) plays a strategic role in instilling religious values while fostering social and ecological awareness among learners. In the context of the global environmental crisis, an ecotheological approach offers a relevant alternative to strengthen spirituality oriented toward environmental preservation. This study aims to examine the implementation of a hadith on cleanliness, particularly the hadith